2003
DOI: 10.1111/j.1444-0938.2003.tb03125.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of myopia§

Abstract: Experiments in animal models of myopia have emphasised the importance of visual input in emmetropisation but it is also evident that the development of human myopia is influenced to some degree by genetic factors. Molecular genetic approaches can help to identify both the genes involved in the control of ocular development and the potential targets for pharmacological intervention. This review covers a variety of techniques that are being used to study the molecular biology of myopia. In the first part, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It has been concerned that accommodative effort required with minus lenses may induce myopia or enhance myopic progression [14]. Schaeffel et al's studies showed that the eyes made functionally hyperopic with negative spectacle lenses became myopic in chicks [25][26][27]. On the other hand, there are controversial assessments in the literature about this issue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been concerned that accommodative effort required with minus lenses may induce myopia or enhance myopic progression [14]. Schaeffel et al's studies showed that the eyes made functionally hyperopic with negative spectacle lenses became myopic in chicks [25][26][27]. On the other hand, there are controversial assessments in the literature about this issue.…”
Section: Discussionmentioning
confidence: 96%
“…Parssinen and Lyyra postulated that constant saccadic eye movements during reading, rather than accommodation and/or convergence, might induce myopic progression causing repeated pressure and stretch pulses on the eye [28]. The development of human myopia is also influenced to some degree by genetic factors [27]. Schaeffel et al [25] showed that accommodation is not necessary for growth that reduces refractive errors during development, and may not be necessary for the normal control of eye growth, at least in chicks.…”
Section: Discussionmentioning
confidence: 99%
“…Much has followed since 14−20 and the purpose of this review is to provide a synopsis of prospects for myopia research in the twenty‐first century. Precedents set by current and previous literature have generated compelling research questions.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Several lines of evidence have demonstrated that genetic factors play an important role in the development of high myopia. 1,[7][8][9] High myopia may be inherited as an autosomal dominant, autosomal recessive, or X-linked recessive trait. 8,10 Linkage studies have mapped at least eight loci (MYP1, MYP2, MYP3, MYP4, MYP5, MYP11, MYP12, and MYP13) responsible for high myopia with Mendelian inheritance, but none of the responsible genes has been identified.…”
mentioning
confidence: 99%